2021
DOI: 10.26444/jpccr/139588
|View full text |Cite
|
Sign up to set email alerts
|

John William Trevan’s concept of Median Lethal Dose (LD50/LC50) – more misused than used

Abstract: Introduction. Median lethal dose (MLD) has been a controversial subject among biologists and animal ethicists since its inception in 1927 by Trevan. Toxicologists use MLD (LD 50 ) as the first step to assess the toxicity of a substance. Animal ethicists criticize LD 50 tests because animals suffer pain, and LD 50 is irreproducible. The disadvantage of classifying chemicals based on LD 50 , the importance of the 'characteristics' proposed by Trevan, and the ideal mortality range for determining the best estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The LD50 was computed using a linear equation and came out to be 5.656g/kg. The results showed a very tiny gain in weight in comparison to mice in the control group, which could be attributed to the oil's toxicity, but the difference in weight between groups is not significant (P ˃0.05) when compared to their control group (Pillai et al, 2021). In their study, Kaithwas et al(2011) found no change in body weight in rats given flaxseed oil intraperitoneally, and this observation is in agreement with the findings of the current investigation into acute toxicity.…”
Section: Discussionmentioning
confidence: 84%
“…The LD50 was computed using a linear equation and came out to be 5.656g/kg. The results showed a very tiny gain in weight in comparison to mice in the control group, which could be attributed to the oil's toxicity, but the difference in weight between groups is not significant (P ˃0.05) when compared to their control group (Pillai et al, 2021). In their study, Kaithwas et al(2011) found no change in body weight in rats given flaxseed oil intraperitoneally, and this observation is in agreement with the findings of the current investigation into acute toxicity.…”
Section: Discussionmentioning
confidence: 84%
“…Both compounds were also evaluated to predict their toxicity with Pro-Tox II software to determine the LD 50 prediction. The LD 50 prediction of both compounds is essential in future research using doses in vivo assay (Pillai et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…One of the most important factors that must be taken into account when researching drugs is to determine the median lethal dose (20), through which you will have an idea of the doses that can be used. We determined the median lethal dose of flurbiprofen using the up-and-down method, which is considered the most ethical method in this approach because a minimum number of animals have been used compared with other approaches (21).…”
Section: Discussionmentioning
confidence: 99%